KARAKTERISTIK PEMERINTAH DAERAH DAN OPINI AUDIT PADA KINERJA KEUANGAN PEMERINTAH DAERAH - Suryaningsih, Ni Made; Sisdyani, Eka Ardhani (E-Jurnal Akuntansi; Vol 15 No 2 (2016), 2016)
This study aims to determine the influence of the characteristics of the local government and audit opinion on the financial performance of local governments in all urban districts in Indonesia. The samples used were as many as 295 districts / cities using purposive sampling method. Data were collected by using the method of documentation. The result show that the prosperity, status, and capital expenditure has no effect on the financial performance, while the level of dependence on the central government and  audit opinion affect the performance of local governments.
Keywords: financial performance, prosperity, status area, the level of dependence on central, capital expenditures, and audit opinion